INDUCTION OF APOPTOSIS IN CANCER CELLS BY PLANTS IN THE GENUS EUPHORBIA - Wongrakpanich, Amaraporn; Charoensuksai, Purin (Thai Bulletin of Pharmaceutical Sciences, 2018)
Euphorbia is an evolutionarily distinct family of plants which have long been used in traditional medicine of diverse cultures to treat various ailments including cancer. In line with their traditional applications, research over the years has supported the anticancer properties of plants in the genus Euphorbia, particularly through their pro-apoptotic activities against various types of cancer cell lines. The aim of this review is to provide a summary of knowledge accumulated over the past few decades regarding the pro-apoptotic activities of the myriad euphorbia species, the chemical structure of isolated compounds and emerging pro-apoptotic mechanisms, as well as discussions relating to the future prospects for research and development of potential anticancer leads from plants in the genus Euphorbia.